Expression of SARS-CoV-2 receptor ACE2 and the protease TMPRSS2 suggests susceptibility of the human embryo in the first trimester. Issue 8 (5th August 2020) - Weatherbee, Bailey A. T.; Glover, David M.; Zernicka-Goetz, Magdalena
Abstract : Abstract : While initially recognized as causing respiratory disease, the SARS-CoV-2 virus also affects many other organs leading to other complications. It has emerged that advanced age and obesity are risk factors for complications but questions concerning the potential effects on fetal health and successful pregnancy for those infected with SARS-CoV-2 remain largely unanswered. Here, we examine human pre-gastrulation embryos to determine the expression patterns of the genes ACE2, encoding the SARS-CoV-2 receptor, and TMPRSS2, encoding a protease that cleaves both the viral spike protein and the ACE2 receptor to facilitate infection. We show expression and co-expression of these genes in the trophoblast of the blastocyst and syncytiotrophoblast and hypoblast of the implantation stages, which develop into tissues that interact with the maternal blood supply for nutrient exchange. Expression of ACE2 and TMPRSS2 in these tissues raises the possibility for vertical transmission and indicates that further work is required to understand potential risks to implantation, placental health and fetal health that require further study.